Integrasi Pendidikan Pesantren dengan Pendidikan Sekolah: Studi di SMP dan Pesantren Bumi Cendekia Yogyakarta - Muhammad Ifan Nur Afuddin (Nusantara: Jurnal Pendidikan Indonesia, 2022)
This study aims to determine the integration system of pesantren education with school education in SMP and Pesantren Bumi Cendekia Yogyakarta as an effort to find out how the education model combines pesantren education with school education. This research uses qualitative methods, namely in-depth case studies of individuals or groups, that are carried out over a relatively long period of time, continuously and with a single object. Data collection techniques were carried out through observation, interviews, and documentation. Test the validity of the data using triangulation of sources and techniques. The data analysis technique was done by transcription, coding, grouping, and comparing and constrating. The pattern of integration systems in SMP and Pesantren Bumi Cendekia is divided into three, namely the concept of an integrated vision and mission, institutional integration; integration of curriculum and learning; and management related to planning, implementation, and evaluation of the integration of pesantren education with school education in SMP and Bumi Cendekia Islamic boarding schools in Yogyakarta.